Laser‐Assisted Thermal Exposure Lithography: Arbitrary Feature Sizes. Issue 5 (3rd March 2021) - Wang, Zhengwei; Zheng, Jinlun; Chen, Guodong; Zhang, Kui; Wei, Tao; Wang, Yang; Liu, Xing; Mo, Zhichang; Gao, Tianyu; Wen, Ming; Wei, Jingsong
Abstract : In traditional optical exposure lithography, the feature size is restricted by the Abbe limit, and it is difficult to obtain patterns with a feature size smaller or larger than the optical spot itself. Herein, a laser‐assisted thermal exposure lithography technique is reported where the feature size can be arbitrarily tuned and changed, and is not limited to the spot size. The minimum feature size of the obtained patterns is 90 nm, which is ≈1/7 of the laser spot size (0.62 μm). The corresponding aspect ratio is ≈1:1. The maximum feature size is 2.7 μm, which is ≈30 times the minimum feature size. A variety of multiscale and multifunctional structures with different feature sizes are obtained successfully through a high‐speed laser‐assisted thermal exposure system, where the writing speed is more than 10 m s −1 . This method offers a pathway for direct laser writing with arbitrary feature sizes, high throughput, and low cost. Abstract : Multiscale structures with different feature sizes are obtained successfully through laser‐assisted thermal exposure lithography. The minimum feature size of the obtained patterns is 90 nm, which is ≈1/7 of the laser spot size (0.62 μm). The maximum feature size is 2.7 μm, which is ≈30 times the minimum feature size.